Job description for information specialist with a degree in library science from Algerian universities: according to Algerian regulations - Boukoffa, Nadia (Journal of Human Sciences, 2021)
Librarianship is benefiting of increasing interest in Algerian university. For a proof of that, the increasing number of the students enrolled in this discipline, and the job-opportunities for the graduated of that scientific field in different public sector, and the important number of legislative and regulatory texts that clarify and define the characteristics of the position held by these university graduated in various Algerian public institutions and administrations, both in library and archives and documentation sectors. In this helpful research, we will try to accompany the students by highlighting the different positions that graduates of the institute and department of librarianship of Algerian university can occupy. Through the existing regulatory texts, we try to specify their exact name, and the required conditions to join them, and those necessary for the promotion to this posts, and other details which are contained in this official texts.